Somalia Country Economic Memorandum : Towards an Inclusive Jobs Agenda - World Bank (World Bank, Washington, DC, 2021)
Somalia has a triple challenge of low levels of labor force participation, low productivity, and high levels of poverty. Economic growth in Somalia has been low, subject to shocks; and thus, insufficient for job creation. Shocks to the economy have contributed to forced displacement, a dominance of jobs outside of agriculture, and rapid urbanization. The Somali economy is largely driven by consumption and supported by external financial flows. In Somalia’s state-building context, enhancing political stability and developing a social contract is fundamental for growth. The objective of the Somalia Country Economic Memorandum (CEM) is to inform the economic policy dialogue and broader debate in Somalia regarding the types of reforms required to stimulate growth and job creation. The Somalia CEM applies and adapts the Jobs and Economic Transformation (JET) Framework. The JET framework has two pillars, one which considers job-creating private investments, and the second that concerns building the capabilities of workers. In the Somali context, efforts have been made to incorporate a gender and inclusion lens, given the particularly low levels of female labor force participation. The report has two special focus chapters on trade and integration and entrepreneurship, due to their importance to growth and jobs in the Somali economy. However, a detailed value chain analysis goes beyond the scope of this report. The report utilizes available quantitative data, primary research conducted for the study, and builds on earlier work. The report considers both the structure of today’s economy and the source of jobs, as well as potential future drivers of growth.